Kontribusi self-efficacy dengan kematangan karier siswa - Febi Febriyanti; Djoni Aminudin (Orien: Cakrawala Ilmiah Mahasiswa, 2022)
in the process of preparing for career maturity, students need to have self-efficacy or self-efficacy, namely the beliefs and beliefs that exist in a person about their abilities. to find out whether there is a relationship between self-efficacy and career maturity of class XII social studies students at SMA Negeri 7 Bekasi. Research Methods The research uses a psychological scale and interviews. The data analysis technique used is descriptive analysis of percentage and product moment correlation. The research sample was 105 students of class XII social studies at SMA Negeri 7 Bekasi. The results of the study can be seen that the results of hypothesis testing indicate that students' self-efficacy has a significant effect on career maturity of class XII Social Studies students at SMA Negeri 7 Bekasi.